CHI3L1 in the CSF is a potential biomarker for anti-leucine-rich glioma inactivated 1 encephalitis - Li, Jinyi; Li, Hongyan; Wang, Yunhuan; Zhao, Xiuhe; Wang, Shengjun; Li, Ling (Frontiers in Immunology, 2023)
Objective Anti-leucine-rich glioma inactivated 1(LGI1) encephalitis is one rare autoimmune encephalitis which is accompanied by inflammatory responses. (Anti-leucine-rich glioma inactivated 1 (anti-LGI1) encephalitis is an autoimmune disease mediated by inflammatory responses.)This study aimed to investigate the Chitinase 3-like 1(CHI3L1) in anti-LGI1encephalitis patients and evaluate its association with modified Rankin Scale (mRS) score in anti-LGI1 encephalitis at admission and 6 months follow-up.(This study looked into the relationship between Chitinase 3-like 1 (CHI3L1) and the modified Ranking Scale (mRS) score in anti-LGI1 encephalitis patients at admission and 6 months later.) Methods Thirty-five patients with anti-LGI1 encephalitis and 22 patients with non-inflammatory neurological disease were enrolled in this study. (We enrolled 35 patients with anti-LGI1 encephalitis and 22 patients with non-inflammatory neurological disease.)Cerebrospinal fluid (CSF) and serum levels of CHI3L1 were measured by enzyme-linked immunosorbent assay. (We quantified CHI3L1 in the serum and cerebrospinal fluid (CSF) by performing an enzyme-linked immunosorbent assay.)Patients were evaluated for mRS score at admission and at 6 months follow-up.(We recorded the mRS score of the patients at admission and 6 months later.) Results CHI3L1 levels in CSF and serum were highly elevated in patients with anti-LGI1 encephalitis at admission compared those with the controls.(At admission, patients with anti-LGI1 encephalitis had elevated CHI3L1 levels in the CSF and serum.) Additionally, patients presenting with cognitive impairment had significantly higher CSF CHI3L1 levels and mRS scores than those without cognitive impairment symptoms. Patients presenting with only faciobrachial dystonic seizures at admission had lower CSF CHI3L1 levels than those with other symptoms. Finally, CSF CHI3L1 levels were positively correlated with CSF lactate levels. Conclusion CHI3L1 level in CSF is correlated with the severity and prognosis of anti-LGI1 encephalitis. (CSF CHI3L1 levels are correlated with the severity and prognosis of anti-LGI1 encephalitis.)